Academic outcome in pediatric ischemic stroke. Issue 6 (17th August 2020) - Champigny, Claire M.; Deotto, Angela; Westmacott, Robyn; Dlamini, Nomazulu; Desrocher, Mary
ABSTRACT: An important cause of acquired brain injury in children, pediatric ischemic stroke can cause sequelae across a wide range of cognitive domains, including verbal reasoning and processing speed. As a result, survivors are especially vulnerable to academic difficulties and face unique challenges compared to their peers. Despite this knowledge, pediatric stroke remains an understudied neurological condition, and its impact on school functioning poorly understood. The present clinical study addressed academic outcome in this population using a multifaceted approach. Patients were recruited for participation from the Children's Stroke Program at the Hospital for Sick Children in Toronto, Canada. A battery of standardized neuropsychological tests was administered, and additional data was collected through parent-rated measures and review of recent academic report cards. Compared to peers, youth with stroke exhibited deficits in processing speed, verbal reasoning, and core academic skills spanning reading, reading comprehension, writing, and math. Lesion laterality did not affect cognitive and academic scores. Youth with a combined cortical-subcortical lesion scored lower on a test of nonverbal reasoning compared to youth with either cortical or subcortical lesions. Compared to healthy peers, the pediatric stroke group was more likely to report requiring extra help at school, accommodations, individual education plans, and assistive technology. They were also more likely to be diagnosed with a learning disability, but not Attention Deficit/Hyperactivity Disorder. Nonverbal reasoning skills, school grades, and school-related quality of life were comparable between groups. The present study contributed to a more nuanced understanding of the impact of pediatric stroke on academic outcome.